2014
DOI: 10.1089/jmf.2013.3088
|View full text |Cite
|
Sign up to set email alerts
|

Lithospermum erythrorhizonExtract Protects Keratinocytes and Fibroblasts Against Oxidative Stress

Abstract: Oxidative stress damages dermal and epidermal cells and degrades extracellular matrix proteins, such as collagen, ultimately leading to skin aging. The present study evaluated the potential protective effect of the aqueous methanolic extract obtained from Lithospermum erythrorhizon (LE) against oxidative stress, induced by H2O2 and ultraviolet (UV) irradiation, on human keratinocyte (HaCaT) and human dermal fibroblast-neonatal (HDF-n) cells. Exposure of cells to H2O2 or UVB irradiation markedly increased oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…[ 8 ] However, most of these results for pharmacological mechanisms were obtained by animal model systems, and only few studies of shikonin in normal human skin cells have been reported. [ 9 10 ] In this study, our aim was to investigate the role of shikonin in the growth of human skin cells and collagen production as an aspect of wound healing promotion by an in vitro study. Moreover, we studied the effect of shikonin on NF-κB pathway in human dermal fibroblasts (HDFs) to elucidate whether NF-κB pathway contributed to anti-inflammatory effect of shikonin.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] However, most of these results for pharmacological mechanisms were obtained by animal model systems, and only few studies of shikonin in normal human skin cells have been reported. [ 9 10 ] In this study, our aim was to investigate the role of shikonin in the growth of human skin cells and collagen production as an aspect of wound healing promotion by an in vitro study. Moreover, we studied the effect of shikonin on NF-κB pathway in human dermal fibroblasts (HDFs) to elucidate whether NF-κB pathway contributed to anti-inflammatory effect of shikonin.…”
Section: Introductionmentioning
confidence: 99%
“…Lithospermum erythrorhizon roots containing shikonin and its derivatives have been widely used for the treatment of wounds, pathogen infections, and tumors (Jang et al 2014) and as natural colorants in food and cosmetic products (Yazaki et al 1999, Yoo et al 2014). The constant increase in a commercial demand for L. erythrorhizon roots and their limited supply from natural resources have promoted the use of biotechnology-based approaches, such as cell or hairy root cultures, for plant conservation and for an enhanced secondary metabolite production (Fujita et al 1981, Shimomura et al 1991, Sykłowska-Baranek et al 2012, Hao et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have hypothesized that medicinal plants, such as Lithospermum erythrorhizon, Panax ginseng, Ginkgo biloba and Rhodiola rosea, may exert beneficial effects on cellular senescence and longevity, which are associated with the aging process (31)(32)(33)(34). Although H. japonicus has been described and used as a traditional remedy in Korea and China, limited information is available with regard to the underlying biological activities, active phytochemicals and action mechanisms of this plant.…”
Section: A B Discussionmentioning
confidence: 99%